Association of inflammation and nutrition-based indicators and diabetic foot ulcers: a cross-sectional study and a retrospective study - Chen, Hua; Zhou, Yu; Dai, Jiezhi (Frontiers in Endocrinology, 2025)
BackgroundInflammation and nutrition status have emerged as important factors in impaired wound healing in diabetes. However, the association between inflammation and nutrition-based indicators and diabetic foot ulcer (DFU) has not been reported.MethodsThis study used a cross-sectional study based on the National Health and Nutrition Examination Survey (NHANES) database and a clinical retrospective study to investigate the association between the inflammation and nutrition-based indicators and DFU. We analyzed data from 31,126 individuals in the NHANES data between 1999 and 2004. Inflammation and nutrition-based indicators included neutrophil–albumin ratio (NAR), monocyte–albumin ratio (MAR), red cell distribution width–albumin ratio (RAR), the hemoglobin, albumin, lymphocyte, and platelet (HALP) score, and prognostic nutritional index (PNI). Binary logistic regression on single and multiple variables and restricted cubic spline were conducted to assess the association and nonlinear relationship between these biomarkers and the prevalence of DFU. Subgroup analyses were performed to evaluate the stability of the associations. Additionally, a retrospective study was conducted to further assess the associations between NAR, MAR, RAR, HALP, PNI, and the prevalence of DFU using binary logistic regression analysis.ResultsA total of 129 participants with DFUs and 1,515 without DFUs were included in this cross-sectional study. NAR, MAR, RAR, HALP, PNI, and DFU are significantly associated with the prevalence of DFU. After adjusting for all covariates (model 3), the third tertile of NAR (OR = 1.73 [1.09–2.74]), MAR (OR = 1.71 [1.05–2.79]), and RAR (OR = 4.47 [2.57–7.77]) were positively linked with DFU, compared with the first tertile. The third tertile of HALP (OR = 0.50 [0.31–0.80]) and PNI (OR = 0.42 [0.26–0.67]), respectively, were negatively linked with DFU compared with the first tertile. The RCS curves showed a nonlinear relationship between RAR and the prevalence of DFU, with an inflection point at 3.83. In the retrospective study, NAR, MAR, and RAR were positively associated with the prevalence of DFU as follows: NAR: OR = 4.71 (1.99–11.18), MAR: OR = 2.56 (1.23–5.31), and RAR: OR = 6.15 (2.31–16.41). On the other hand, HALP and PNI were negatively linked with the risk of DFU (HALP: OR = 0.93 [0.90–0.97] and PNI: OR = 0.85 [0.78–0.93]).ConclusionHigh NAR, MAR, and RAR were positively associated with the prevalence of DFU, whereas low HALP and PNI were linked with an increased prevalence of DFU. In addition, RAR performed better in terms of predictive ability.